2015
DOI: 10.1111/jrh.12146
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Primary Care Service Patterns by Rural‐Urban Location

Abstract: Primary care physicians who value practicing a relatively diverse range of services may find locating in rural areas an appealing choice. Health systems and policy makers seeking to attract primary care physicians to rural areas can incorporate this reality into a recruitment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…We are not aware of any studies concerning practice variation of surgical and gynaecological procedures by GPs inside PHC, but our findings of sizeable variations in services provided by health care providers is in line with other studies in this research field [13, 5, 7, 8, 25]. The main determinant of practice variation in our study was GP gender.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We are not aware of any studies concerning practice variation of surgical and gynaecological procedures by GPs inside PHC, but our findings of sizeable variations in services provided by health care providers is in line with other studies in this research field [13, 5, 7, 8, 25]. The main determinant of practice variation in our study was GP gender.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding our findings that GPs working in the largest municipalities have lower odds of performing major surgical procedures, this seem to align well with a study from Iowa. Here, GPs working in nonmetropolitan settings performed more services including surgical procedures than GPs working in metropolitan areas [25]. Interestingly, Rivet et al found that a larger range of procedures was associated with a higher level of job satisfaction among primary care physicians [29].…”
Section: Discussionmentioning
confidence: 99%
“…– 11 However, in recent years, strategies have been implemented at the regional, state, and federal levels to increase the number of providers practicing in rural healthcare 1215 In addition, the care environment has changed in the last decade as a result of the increased use of internet applications and advanced communication technologies 16.…”
Section: Introductionmentioning
confidence: 99%
“…Additional barriers to accessing specialty care for minor illnesses during cancer treatment or health maintenance during survivorship may include household material hardship 36,37 and the absence of infrastructure such as mass transit in rural areas. 41 We also found that physicians were significantly more comfortable than advanced-level practitioners in providing acute medical care to on-therapy patients, suggesting that more extensive training may have an impact on comfort level in caring for patients with complex chronic illnesses. Despite the large percentage of PCPs reporting the recent provision of care for patients with childhood cancer and/or survivors in their practices, we found that less than one-half were comfortable in providing such care independently, and that the majority desired collaboration with pediatric oncologists.…”
Section: Discussionmentioning
confidence: 62%
“…This may reflect the general practice patterns in rural primary care, in which providers are more likely to perform services that would be performed by specialists in an urban area. 41 We also found that physicians were significantly more comfortable than advanced-level practitioners in providing acute medical care to on-therapy patients, suggesting that more extensive training may have an impact on comfort level in caring for patients with complex chronic illnesses. 42 Provider experience (older age and larger number of patients seen per week) was associated with greater comfort in independently providing health maintenance care to survivors.…”
Section: Discussionmentioning
confidence: 62%